Fractional of sky cover at Shah Alam / Rahimah Abdul Rahim - Abdul Rahim, Rahimah (2009)
This research presents the fractional of sky cover at Shah Alam. Sky cover means the expected amount of clouds (in percent) covering the sky valid for the indicated hour. To know the fractional of sky cover, the new instrument named Total Sky Imager ModelTSI-880 was used to capture the sky cover. This is one of the automated processing methods in order to determine the fractional of sky cover. The factors that consider influencing the fractional of sky cover are the characteristics of Malaysia's climate which is constantly high temperature and relatively humid throughout the year. This is mainly due to the formation of the cloud. Clouds remain the greatest source of uncertainty in global climate change research. Sky condition has similar features and is useful for energy-efficient building designs. Fractions of sky cover are divided into three; clear sky, thin, and opaque. It measured in tenths, which are 0.0 to 0.3 indicates for clear sky, 0.4 to 0.7indicates thin, and 0.8 to 1.0 indicates opaque.